Design of fuzzy logic controller for temperature control of small-scale food storage. (August 2019) - Latif, M; Muharam, M; Darmawan,; Darwison,; Costa, R R
Abstract: A Fuzzy Logic Controller (FLC) is developed to control the temperature of small-scale food storage. The FLC has two components such as the algorithm part and the hardware part. For the algorithm part, The FLC takes two input parameter such as the temperature and the humidity of the storage and takes one output parameter such as the speed of the fan. The membership function is designed as following hot, fair, cold, and too cold as for the membership functions of the temperature parameter. For the humidity membership functions are dry, dry enough, normal, less moist, and moist. As for the fan speed, the membership functions are fast, less fast, fair, slow, and too slow. On the other hand, for the hardware, the DHT11 senses the temperature and the humidity. For the cooling process, thermoelectric is used to decrease the temperature. The results show that the FLC can be used to control the temperature of the storage to achieve as the minimum temperature as 12.5°C.